Al-Tadlīl ‘alā Imāmah Abī Bakr min Khilāli Tafsīr al-Māturīdī - Ünsal, Hadiye (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
Abū Manṣūr Muḥammad b. Maḥmūd al-Samarḳandī (d. 333/944), the founder of the Māturīdiyya sect, is one of the significant scholars of the Hanafi sect. Imam Māturīdī is a scholar in the history of Islamic science who became famous for a theologian (mutaqallim), interpreter (mufassir) and jurist (faqīh), and is known for his Kitāb al-Tawḥīd. Besides that, Māturīdī and his commentary entitled Taʼwīlāt al-Qurʼān - one of the earliest tafsir bi al-ra’y (bi-al dirayah) examples of the exegetical literature- have broadly been studied in Turkish theology academia especially in recent years. This study aims to discuss the verses related to Abū Bakr’s (d. 13/634) caliphate in Imam al-Māturīdī’s Taʼwīlāt al-Qurʼān in terms of the distinction between tafsir and ta’wil. As it is known, the distinction between tafsir and ta’wil is based on Māturīdī’s writings. According to this distinction, tafsir is the process of interpretation particularly by the companions whereas ta’wil is done by the fuqaha. Therefore it is appropriate to say that tafsir means “contextual meaning” while ta’wil stands for “commentation.” As a matter of fact, Māturīdī also explains the word tafsir as the first and original meaning of the Qur’an in the context of its revelation. However, he explains in his Taʼwīlāt al-Qurʼān many verses by associating them with some issues that emerged after the revelation of the Qur’an, thus making “ta’wil.” Moreover, he gave the title Taʼwīlāt to his work in accordance with this understanding. In this study, it will be discussed whether Māturīdī’s well-known definition of tafsir contradicts or not with his commentation on the verses that he claims pointing to Abū Bakr’s caliphate and/or his superiority. The verses considered evidence for Abū Bakr’s caliphate and/or his superiority in Taʼwīlāt al-Qurʼān will be scanned and in this context, the way Māturīdī understands and interprets verses such as al-Maidah 5/54, at-Tawbah 9/40, Hūd 11/84 and al-Hadid 57/19 will be analyzed.